Risk Evaluation in Software Project Using Bayesian Network Modeling (Research, Society and Development, 2020)
Project risk events are often influenced by each other and rarely act independently. In this context, effective methods to identify, model and analyze these risks are necessary. The objective of this article is to apply the risk analysis in a software development project, based on the model of the Software Engineering Institute (SEI), using the Bayes model to calculate the event probabilities and also the Noisy-OR calculation structure to assign the initial weights of the network of factors that influence the project. In this way, it is expected to increase the chances of success of the risk analysis process. The results obtained by the techniques adopted prove to be promising in assisting the process of decision making by the managers of software development projects.